Development of software to interpretate radiographs of F5 wing spars focussing on crack recognition - Seah, Daphne Xinrui. (2013)
The Republic of Singapore Air Force (RSAF) is developing an automated digital radiography system which comprises an automated crack detection software, to identify cracks on the F5 wing spars.